Analisis Putusan Hakim Dalam Perkara Tindak Pidana Kekerasan Seksual Terhadap Anak (Studi Kasus Nomor 1941/Pid. Sus/2024/PN Sby) - Fatimah Nur Fauzia; M. Syahrul Borman; Dudik Djaja Sidarta; Noenik Soekorini (JOURNAL OF SHARIA ECONOMICS, 2022)
Sexual violence against children is a serious form of human rightsviolation with widespread physical, psychological, and social impacts.This study aims to analyze the judge's considerations in issuing averdict in a case of sexual violence against children based on CaseStudy Number 1941/Pid.Sus/2024/PN Sby, and assess itscompliance with the provisions of the Child Protection Law. Themethod used is a normative juridical approach using primary andsecondary data sources, including court decisions and relevant lawsand regulations. The results show that the judge considered two mainaspects in issuing a verdict: legal considerations (such as charges,evidence, and violated articles) and non-legal considerations (suchas the victim's psychological condition, the defendant'ssocioeconomic background, and morality factors). In this case, theperpetrator was sentenced to six years in prison and a fine ofRp50,000,000.00 for being proven to have committed sexual violenceagainst children. This verdict reflects efforts to protect child victimslegally, although there is still room for evaluation regarding theoptimization of aspects of restorative justice and victim rehabilitation.This research is expected to contribute to the development of juvenilecriminal law and the evaluation of judicial practices regarding sexualcrimes targeting vulnerable groups.